2016
DOI: 10.1002/anie.201609073
|View full text |Cite
|
Sign up to set email alerts
|

Chirality‐Assisted Synthesis of a Very Large Octameric Hydrogen‐Bonded Capsule

Abstract: The strategy of chirality-assisted synthesis, which makes use of enantiomerically pure building blocks that are designed to associate in a single geometric orientation, was applied to synthesize an octameric hydrogen-bonded capsule with a cavity volume of 2300 Å . This cube-shaped capsule forms even host-guest complexes with tetraalkylammonium ions, and accommodates the large tetrahexadecylammonium cation in its cavity. The use of an enantiopure building block was shown to be highly beneficial for capsule form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 114 publications
3
59
0
Order By: Relevance
“…NEt 4 + is complexed by all three cages with significantly smaller association constants dropping several orders of magnitude, clearly revealing that separation of solvent‐shared ion pairs is negatively contributing to the overall Coulomb term of interaction. Similar observations were made before for other host systems . The smallest change has been observed for NPr 4 + .…”
Section: Resultssupporting
confidence: 89%
“…NEt 4 + is complexed by all three cages with significantly smaller association constants dropping several orders of magnitude, clearly revealing that separation of solvent‐shared ion pairs is negatively contributing to the overall Coulomb term of interaction. Similar observations were made before for other host systems . The smallest change has been observed for NPr 4 + .…”
Section: Resultssupporting
confidence: 89%
“…Numerous chiral hosts based on covalent macrocyclic molecules such as cyclodextrins, cyclophanes, and calixarenes have been reported . Chirality has also been reported to facilitate the assembly of hydrogen‐bonded organic cages . More recently, chiral metallo‐supramolecular self‐assembled rings and cages have been introduced as selective receptors and enzyme‐like nanoreactors based on chiral backbones, auxiliaries, the inherent chirality of stereogenic metal centers, or the overall architecture .…”
Section: Figurementioning
confidence: 99%
“…23 Chirality of organic cages would open new research directions towards asymmetric applications, but the number of such molecules is limited. 2,3,24,25 In this paper we present a new member of the family of organic nanocages that has unique features, originating from its chirality, covalent, rigid skeleton and presence of moleculesized portals.We have previously shown that tetraformylresorcin[4]arene 1 26 reacts easily with monofunctional amines and hydrazides leading to formation of respective imines (quantitatively tautomerized to keto-enamines) 27 and acylhydrazones. 28 Both types of products are stabilized by directional seams of intramolecular hydrogen bonds, which, in addition to stabilization, results in inherent chirality of the molecules.…”
mentioning
confidence: 99%
“…23 Chirality of organic cages would open new research directions towards asymmetric applications, but the number of such molecules is limited. 2,3,24,25 In this paper we present a new member of the family of organic nanocages that has unique features, originating from its chirality, covalent, rigid skeleton and presence of moleculesized portals.…”
mentioning
confidence: 99%